Blower-Powered Soft Inflatable Joints for Physical Human-Robot Interaction - Niiyama, Ryuma; Seong, Young ah; Kawahara, Yoshihiro; Kuniyoshi, Yasuo (Frontiers in Robotics and AI, 2021)
The inflatable is a safe and lightweight structure even at the human scale. Inflatable robots are expected to be applied to physical human-robot interaction (pHRI). Active joint mechanisms are essential for the development of inflatable robots. The existing mechanisms are complex in structure and difficult to integrate actuators, preventing the advantages of inflatables. We propose blower-powered soft inflatable joints that are easy to fabricate and have space for an actuation inside. The joints are driven by tendon wires pulled by linear actuators. We derived a theoretical model for both unilateral and bilateral joints. We demonstrated a hugging robot with multiple joints as an application of the proposed joint mechanism. The novelty of the proposed joint mechanism and the inflatable robot is that rigid parts have been thoroughly eliminated and the tendons for actuation have been successfully hidden inside. The active control of internal pressure makes it resistant to punctures. We expect that the contact safety of inflatable robots will facilitate the growth of the pHRI field.